Estudo de aspectos básicos da física e química do estado sólido - Matos, Heveson Luís Lima de (2016)
In this work a contribution to basic knowledges of physical and chemistry of the solid state is presented. Based on fundamental concepts of physical chemistry, such as charge distribution, electronegativity and electric dipole moment of the compounds, a purely analytical expression for obtaining the effective atomic number (Zeff ) and a general way to get the crystal packing factor, p, of any ionic system is being presented. The local interaction cation-anion occurs between the electronic clouds of the outermost electrons. So, we are postulating an effective separation (Rij ) between the negative and positive centre of charge of two ways; in one of them Rij is related to the electric dipole moment and the electronegativity difference, and the other by the average difference between the atomic and ionic (crystalline) radii of the interacting ions. When compared to the experimental data analyzed, predictions of up to 20% have been obtained for the Zeff of diatomic materials (BeO, LiF, Al2O3, MgO, NaF, SiO2, CaF2, V2O3 and ZnO) and above 20% for polyatomic crystals (Li2B4O7 and CaSO4) applied in dosimetry. In photonics, the increasing behavior of the refractive index with Zeff for the glass system (0.7-x)NaPO3-0.3WO3-xBi 2O3 is confirmed. By combining crystal field and effective charge models, we have done predictions of Zeff for the system Eu2O3 within the range of experimental data analyzed. Also we are proposing an analytical expression to calculate the photoionization cross-section (SCF) of isotropic defects or impurities centers, by using the time-dependent perturbation theory. The ground-state wavefunction of the electron captured in the impurity state is described by a three-dimensional isotropic harmonic oscillator and the excited electron in the continuum conduction band is described by a plane wave. The expression has been obtained considering all multipoles terms in the Hamiltonian, and that the radiation field which interacts with matter is semi-classical and linearly polarized. This approximation is assumed because the linear effects are dominant. The model is applied to predict the SCF of the Al2O3:C and Lu2SiO5: Ce crystals, and the predictions are in good agreement with the available data in the literature.